2002
DOI: 10.1124/dmd.30.12.1352
|View full text |Cite
|
Sign up to set email alerts
|

Gemfibrozil Inhibits CYP2C8-Mediated Cerivastatin Metabolism in Human Liver Microsomes

Abstract: ABSTRACT:To explore the mechanism of the interaction between gemfibrozil and cerivastatin, the enzyme mapping of the oxidative metabolism of cerivastatin and the effect of gemfibrozil on cerivastatin metabolism were studied using human liver microsomes and expressed cytochrome P450 (P450) CYP2C8 and 3A4 isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 18 publications
6
159
1
2
Order By: Relevance
“…Fluvoxamine 0.06-0.23 (Schulz et al, 2012) 0.2-0.7 0.2 (Brosen et al, 1993) Amiodarone 0.5-2.5 (Schulz et al, 2012) 0.7-3.9 86 (Kobayashi et al, 1998) Efavirenz > 1 (Schulz et al, 2012) > 3.2 6 (Xu and Desta, 2013) Gemfibrozil 25 (Schulz et al, 2012) 91 (Wang et al, 2002) Fluconazole 1-5 (Schulz et al, 2012) 4.9-16.3 30.3 (Niwa et al, 2005) Chloramphenicol 5-10 (Schulz et al, 2012) 15.5-31 32 (Park et al, 2003) Fluoxetine 0.12-0.5 (Schulz et al, 2012) 0.4-1.6…”
Section: Known Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluvoxamine 0.06-0.23 (Schulz et al, 2012) 0.2-0.7 0.2 (Brosen et al, 1993) Amiodarone 0.5-2.5 (Schulz et al, 2012) 0.7-3.9 86 (Kobayashi et al, 1998) Efavirenz > 1 (Schulz et al, 2012) > 3.2 6 (Xu and Desta, 2013) Gemfibrozil 25 (Schulz et al, 2012) 91 (Wang et al, 2002) Fluconazole 1-5 (Schulz et al, 2012) 4.9-16.3 30.3 (Niwa et al, 2005) Chloramphenicol 5-10 (Schulz et al, 2012) 15.5-31 32 (Park et al, 2003) Fluoxetine 0.12-0.5 (Schulz et al, 2012) 0.4-1.6…”
Section: Known Inhibitorsmentioning
confidence: 99%
“…A tryptamine concentration of 100 µM was chosen because at that concentrations, no or only slight inhibition could be considered as clinically irrelevant. Clinically relevant inhibitors showed IC50 values of about 100 µM (Bertelsen et al, 2003;Brosen et al, 1993;Burt et al, 2010;Ewald and Maurer, 2008;Kobayashi et al, 1998;Niwa et al, 2005;Park et al, 2003;von Moltke et al, 1998;Wang et al, 2002;Xu and Desta, 2013). Therefore, the IC50 values were only determined for TDNPS that showed inhibition of more than 50%.…”
Section: Prescreening and Determination Of Ic50 Valuesmentioning
confidence: 99%
“…Repaglinide is completely metabolised, and cytochromes P-450 (CYP) 2C8 and 3A4 participate in its biotransformation in vitro [2]. Fibrates like gemfibrozil are widely used in the treatment of diabetic dyslipidaemia, and gemfibrozil was recently found to inhibit CYP2C8 [3,4]. Several commonly used drugs, such as the antimycotic itraconazole, are inhibitors of CYP3A4 [5].…”
mentioning
confidence: 99%
“…CYP2C8 is a pivotal enzyme in the catalyzing pathway of cerivastatin that is also highlighted by the recent report showing that the drug gemfibrozil, when interacting with cerivastatin, inhibits CYP2C8 activity in human liver microsome (Wang et al 2002). The patient most likely lacks the enzyme activity of CYP2C8 due to the homozygous mutation of 475delA that loses 64% of the protein structure.…”
Section: Resultsmentioning
confidence: 97%
“…However, despite the dual metabolizing pathways, cerivastatin caused rhabdomyolysis more frequently than other statins, especially when cerivastatin was given together with other drugs such as gemfibrozil (Farmer 2001;Staffa et al 2002). In vitro experiment with human liver microsome demonstrated that gemfibrozil inhibited CYP2C8 activity leading to a decreased level of M-23 in the cerivastatin-metabolizing pathway, which at least partially explains the interaction between gemfibrozil and cerivastatin (Wang et al 2002). Because of the adverse effects in the muscles causing rhabdomyolysis, cerivastatin was withdrawn from the market in August 2001.…”
Section: Introductionmentioning
confidence: 99%